The bioconversion of faecal and kitchen waste using black soldier fly larvae (Hermetia illucens): : mass balance process (African Journal of Science, Technology and Social Sciences, 2024)
Novel technologies to convert faecal waste into valuable nutrients provide a win-win situation in enhancing the closed sanitation loop, and providing safe sanitation. In this study, laboratory-scale experiments were set to examine the applicability of the Black Soldier Fly in bioconversion of organic matter (faecal matter (FM) and kitchen waste (KW) while producing larvae biomass rich in protein and fat compounds. To determine the mass balance process, each of the feed substrates (500g) in triplicate and 3 grams of 6-day-old larvae (844 larvae) were introduced. The larval developmental time to 50% pupation, survival rate (SR), waste reduction rates (WR), prepupal yield, bioconversion rate (BCR), feed conversion rate (FCR), and efficiency of digested feed (ECD) were monitored in triplicate at the end of the experiments for mass balance process. Mass balance determination (triplicate) yielded average prepupal yield of 70.43±0.02g and 56.77±0.01g, with protein content per unit ranging from 32.23% to 41.26% and 20.06% to 37.13% on faecal and kitchen waste respectively. The ECD of 17.63±0.01% and 12.05±0.00%, waste reduction of 79.91% and 92.24% from faecal and kitchen waste respectively were obtained. From the findings, both substrates were palatable as BSFL feeds. The study findings show the potential of using BSF larvae technology to valorise faecal and kitchen waste and produce larval biomass rich in proteins and fats.
Keywords: SANITATION; fecal matter; waste management